2014
DOI: 10.1155/2014/249372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bax and Bak Gene Mutations and Expression in Breast Cancer

Abstract: Genetic analyses have provided evidence to suggest that Bax and Bak are the essential genes for apoptosis in mammalians cells. This study aimed to search for biomarkers in breast cancer to be used as prognostic markers for the disease. The Bak and Bax genes expressions were analyzed in 23 breast cancer patients by RT-PCR technique. SSCP technique was used to detect the mobility of the abnormal fragment in Bak exon 4. PCR for Bax promoter was digested with Tau 1 restriction enzyme to identify a single polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
2
19
0
3
Order By: Relevance
“…Furthermore, mutations of Bax exons lead to chemoresistance. Bax gene mutation is highly involved in various types of human cancer . Moshynska et al reported the effect of promoter SNP in the human Bax gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutations of Bax exons lead to chemoresistance. Bax gene mutation is highly involved in various types of human cancer . Moshynska et al reported the effect of promoter SNP in the human Bax gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…The results so far indicate that the model that we have generated reflects the behaviour of the intrinsic apoptotic pathway and therefore can be used to analyse the relative contributions of BAX and SMAC to the irreversible activation of the system. Importantly, these proteins have been shown to be deregulated in several diseases such as cancer and neurodegeneration, where incorrect activation of apoptosis are hallmarks 4,6,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . In the case of tumour cells, it has been shown that there is an increase of the threshold of apoptosis activation by downregulation of BAX and SMAC 16,31,35 .…”
Section: Bax and Smac Regulate The Threshold And Amplitude Of The Apomentioning
confidence: 99%
“…Models developed including BAX and SMAC have shown that these proteins are key in the regulation of apoptotic commitment. BAX is the gateway to mitochondrial activation of intrinsic apoptosis and has been shown to form pores in the mitochondrial membrane resulting in the release of pro-apoptotic proteins [26][27][28] . SMAC is one of the proteins released from the mitochondria upon activation of the intrinsic apoptotic pathway and is and inhibitor of IAPs 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, varios estudios han informado que el polimorfismo G(-248)A en el promotor de Bax (Figura 19), podría ser utilizado como un biomarcador de susceptibilidad o protección al cáncer, mientras que otros no han encontrado asociación alguna (Sahu y Choudhuri, 2013;Saxena et al, 2002;Skogsberg et al, 2006). En pacientes con leucemia linfocítica crónica se ha encontrado que este SNP se asocia con la reducción en la expresión proteica, estadio avanzado de la enfermedad y una respuesta incompleta al tratamiento (Kholoussi et al, 2014).…”
Section: Polimorfismos En Los Promotores De Los Genes Bax Y Bcl-2unclassified